Strategi Bauran Pemasaran 4P Produk Gadai Emas pada Pegadaian Syariah - Nuris Tishwanah; Rasyid Abi Sandi; Nurul Auliyah Bakri (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2023)
This study aims to determine the most appropriate marketing mix strategy to be used and applied in Sharia pawnshops to increase the sales volume of gold pawn products. This research uses a qualitative research method with a SWOT analysis approach because it is based on an assumption that states that an effective strategy can maximize the opportunities and strengths that exist in product suau, one of which is gold pawn products in Sharia pawnshops. Then further analysis is carried out using EFAS and IFAS techniques and the results will be outlined in a cartesius diagram. The results of the SWOT analysis state that gold pawn products at Sharia pawnshops are in quadrant I expansion, which means that sharia pawnshops are in prime condition which allows them to expand, achieve maximum progress, and increase growth. This research focused on gold pawn products in Sharia pawnshops that are in great demand by the public.